2016
DOI: 10.5604/12321966.1226851
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Toxoplasma gondii and Neospora caninum in goats from north-western Spain

Abstract: Introduction and objective. Toxoplasma gondii and Neospora caninum are protozoans involved in reproductive failure especially in ruminant livestock. The objective was to estimate the seroprevalence of both parasites in goats from northwestern Spain and to study the influence of some factors on seropositivity. Materials and method. Blood samples from 638 goats were collected in 50 farms. Presence of T. gondii and N. caninum antibodies were detected by direct agglutination and competitiveELISA techniques, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 24 publications
(37 reference statements)
1
8
0
Order By: Relevance
“…These environmental factors could be beneficial to the sporulation, viability and spread of T. gondii oocysts ( 31 ). Previous studies indicated that annual temperature and rainfall could facilitate the survival of the environmental T. gondii oocysts, and seasonally or permanently pasture goats as well as increases the contact between goats and the oocysts ( 32 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…These environmental factors could be beneficial to the sporulation, viability and spread of T. gondii oocysts ( 31 ). Previous studies indicated that annual temperature and rainfall could facilitate the survival of the environmental T. gondii oocysts, and seasonally or permanently pasture goats as well as increases the contact between goats and the oocysts ( 32 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Flock-level prevalence was reported as 12-50% in Jordan (1, 2), 13.3% in Iran (15), 32.1% in Italy (14), 0.9% in Poland (9), 38% in Spain (11), 53.2% in Argentina (26) and 16.4-75.2% in Brazil (5,33). In this study, we determined the flock-level prevalence as 66.6% (10/15), which is higher than the abovementioned rates, except for Brazil (5).…”
Section: Tab 2 Serological Studies On Caprine Neosporosis In Differmentioning
confidence: 99%
“…These seroprevalences were much lower than those of antibodies against T. gondii in both species (i.e., 66.3% and 50.5% in sheep and goats, respectively). High seroprevalences for T. gondii and lower antibody prevalences for N. caninum were also found in other European countries when testing small ruminants simultaneously for both parasites: i.e., in Greece ( Diakou et al, 2013 ), Romania ( Iovu et al, 2012 ), Slovakia ( Spilovská et al, 2009 ; Čobádiová et al, 2013 ) and Spain ( Díaz et al, 2016 ; Ruiz-Fons et al, 2014 ), suggesting a general lower exposition to N. caninum . In Switzerland there are more than three times more domestic cats than dogs registered (1,634,000 vs. 506,000 in 2018) ( Schultz, 2019 ) ( https://de.statista.com/themen/3748/haustiere-in-der-schweiz/ ), which could account for a potential higher environmental contamination with T. gondii than with N. caninum oocysts.…”
Section: Discussionmentioning
confidence: 65%
“… (b) kids (< 6 months). N. caninum DNA was detected in blood from 14/18 Neospora -seropositive animals ( Čobádiová et al, 2013 ) Spain Galicia ELISA (cELISA Neospora caninum Antibody Test Kit, VMRD, USA) 45/638 6.0 19/50 38.0 Male and female Cabra Galega and crossbred goats, different ages, extensive and semi-extensive husbandry system ( Díaz et al, 2016 ) Switzerland Country-wide ELISA (ID Screen® Neospora caninum Indirect (ID.vet, France) + immunoblot (in house) of inconclusive sera 7/748 0.9 3/164 1.8 Randomly sampled general goat population, healthy animals, different sex and ages This study ELISA: Enzyme-linked immunosorbent assay; cELISA: competitive ELISA; IFAT: indirect fluorescent antibody test; ns: not specified. …”
Section: Discussionmentioning
confidence: 99%